Subcutaneous Allergen Immunotherapy With Thermosensitive Hydrogel and Recombinant Birch Pollen Allergen Variant, a Randomised Controlled Trial - Anna Nilson; Patricia Couroux; Jaana Haka; Silja Halme; Pekka Mattila; R. J. Joost van Neerven; Rolien Pels‐Rijcken; Janneke Ruinemans‐Koerts; Yvonne Schmidt‐Hieltjes; Anne Marie Salapatek; Kati Sallinen; Kristiina Takkinen; et al. (Clinical & Experimental Allergy, 2026)
ABSTRACT Background This paper reports a Phase 1, randomised, placebo‐controlled, dose‐escalation trial (NCT06037148) with DM‐101PX that contains a recombinant hypoallergenic Bet v 1 variant formulated with thermosensitive hydrogel. The objectives of the study included assessment of treatment‐related adverse events and the number of participants reaching the maximum dose. In addition, Bet v 1‐specific immunoglobulins were analysed to explore the immunological effects of treatment. The trial was funded by Desentum Oy. Methods The study included three cohorts differing in starting and maximum dose. Per cohort, subjects were randomised (4:1) to receive 10 weekly subcutaneous injections with DM‐101PX or placebo. Main inclusion criteria comprised adult subjects with a birch pollen allergy for ≥ 2 years, positive skin prick test, birch pollen‐IgE ≥ 0.7 kU/L and symptoms upon exposure to birch pollen. The randomisation schedule was generated using software. During the trial, the investigator, clinic staff, participants and sponsor remained blinded to the treatment groups. The primary endpoint was the occurrence of treatment emergent adverse events and adverse events of special interest. Results In each cohort, 10 subjects were randomised and all were used for analysis of safety data. Treatment‐related adverse events were reported by 22/24 (91.7%) DM‐101PX treated subjects and by 5/6 (83.3%) placebo‐treated subjects, which were only of mild or moderate intensity. The DM‐101PX and placebo‐treated subjects had mainly local injection site reactions, 138/153 (90.2%) and 22/24 (91.2%), respectively. Fifteen systemic allergic reactions were reported by 5/24 (20.8%) DM‐101PX‐treated subjects, and 2 systemic allergic reactions were reported by 1/6 (16.7%) placebo‐treated subject, all of which were of Grade 1. 21/24 (88%) of subjects reached the maximum dose. Treatment with DM‐101PX induced pronounced levels of Bet v 1‐specific IgG 4 and post‐treatment sera effectively blocked basophil activation. Conclusions This small study demonstrated that DM‐101PX was generally well tolerated and induced a strong and functional immune response.